Efek Moderasi Kontrol Diri pada Hubungan Sifat Materialisme Terhadap Pembelian Impulsif Online - Dessy Balik; Fenri Abraham Stevi Tupamahu (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2020)
This study aims to (1) examine the effect of materialism on impulsive online purchases. (2) To examine themoderating effect of self-control on the relationship between materialism and impulsive online purchases. This type ofresearch is a causal research. The unit of analysis in this study is an individual lecturer at the Indonesian Christian Universityof Maluku (UKIM) as online shopping consumers who have made impulsive purchases online. The sampling method usingnonprobability method, sampling using purposive sampling technique with the final sample of 48 people. Data analysisused thThe results of the study prove that materialism has an effect on impulsive online purchases.The results of the study prove that materialism has an effect on impulsive online purchases. The nature of UKIMlecturers as consumers who emphasize the value of material, are selfish, want to have a lot of goods, and feel thatownership does not increase happiness, so that thoughtless buying behavior as a result, spontaneous purchases, rushpurchases, and purchases are influenced by emotional states will increase . Consumers who have materialisticcharacteristics are classified as young consumers and have a high tendency to interact with social media with the potentialto do impulsive shopping online. This study proves the impact of moderation of self-control as controlling consumer behaviorin terms of valuing goods based on symbolic goods, social status, building social status from purchasing an item, andexcessive prestige. The impact of self-control moderation has been shown to contribute to the influence of materialism onimpulsive online purchases.